Reaksi pasar atas pengumuman peringkat kinerja perusahaan dalam pengelolaan lingkungan - Wiranata, I Wayan Eka (E-Jurnal Akuntansi; Vol 8 No 3 (2014), 2014)
This research is an event study that discusses the market reaction as a result of any information regarding the company's announcement of performance ratings in managing the environment by PROPER program. The purpose of this study was to determine whether the market reacted to the announcement of the PROPER ratings indicated the presence of abnormal returns around the announcement date. The data used in this study are daily stock prices of companies that participated in the program. The observation in this study for 7 days and the methods used to analyze the data is one sample t - test. The results of this study revealed that there are significant abnormal returns during the announcement date and the second day after the date of the announcement. This shows that investors react when the announcement about the company's environmental performance rating. Positive abnormal return indicates that this announcement is good news that the performance ranking programs on the environment should be carried out again.
Keywords: market reaction, abnormal return, environmental performance, proper